2017
DOI: 10.1177/0268355517721055
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative mechanism in the course of varicose veins

Abstract: Objective Our objective was to evaluate the state of oxidative stress in the great saphenous varicose vein wall and blood of varicose vein patients taken from the antecubital vein. Methods The superoxide dismutase, reduced glutathione (GSH) and total antioxidant status were measured with commercially available colorimetric kits in erythrocytes, plasma and varicose vein wall of 65 patients (second degree of clinical state classification, etiology, anatomy and pathophysiology) aged 22-70 (49 women, 16 men) in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(39 reference statements)
0
16
1
Order By: Relevance
“…Research findings studying the Gpx and GST, and thus GSH levels in tissue homogenates of VVs and their association with the disease are controversial. 6,26,31,32 In our study, CAT levels were found to be higher than the control group. In the context of the study, MDA and CAT levels were found to be higher than control group and SOD, GPx and GST levels were found to be lower than the control group.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…Research findings studying the Gpx and GST, and thus GSH levels in tissue homogenates of VVs and their association with the disease are controversial. 6,26,31,32 In our study, CAT levels were found to be higher than the control group. In the context of the study, MDA and CAT levels were found to be higher than control group and SOD, GPx and GST levels were found to be lower than the control group.…”
Section: Discussioncontrasting
confidence: 40%
“…Research findings studying the Gpx and GST, and thus GSH levels in tissue homogenates of VVs and their association with the disease are controversial. 6,26,31,32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e main destructive factor is venous hypertension, which may lead to the remodeling of vein walls and vein valves due to an increase in venous pressure, which leads to structural and functional changes in the vein wall. Various studies have hypothesized that the cause of CVD is the trapping of leukocytes owing to the defective valves and oxidative stress in the veins [3][4][5]. In addition, hypoxia performs a significant role in the physiopathology of varicose veins [6].…”
Section: Introductionmentioning
confidence: 99%